Analisis Kesesuaian Lahan Pertanian Untuk Rekomendasi Pengendalian Alih Fungsi Kawasan pertanian Kecamatan Bantimurung, Kabupaten Maros. - Putri Dwi Wulandary; Rahmawati Rahman; Emil Salim Rasyidi (Journal of Urban Planning Studies, 2022)
Abstract. The purpose of this research was to determine the suitability of agricultural land in Bantimurung District, to provide the concept of controlling land use change in agricultural areas in Bantimurung District. This research used quantitative research using the overlay method on the unit map of land capability, land development capability, agricultural spatial planning directions, then analyzed by analysis of suitability between spatial planning and agricultural development directions. Based on the result obtained in the direction of land suitability, it has been found that in Bantimurung District is divided into two classes, namely annual crop and perennial crop. For the recommendation concept of controlling the conversion of agricultural areas in the designation of spatial patterns with Non KP2B status, it is directed to limit activities, activity radius, and control waste that threatens agricultural activities, while for the designation of spatial patterns with KP2B status, it is directed not to allow the conversion of agricultural land become non-agricultural areas. in accordance with PP No.1 of 2011 and also directed to the protection of agricultural areas and food land areas from land conversion.